Grumpy monkey ready, set, bananas! - Lang, Suzanne; Lang, Max 1982- (New York Random House, 2021)
Jim Panzee begrudgingly agrees to help Tortoise enter the big race
English Stories
Ages 4-6
Grades K-1
Keywords: Animals -- Fiction; Chimpanzees -- Fiction; Racing -- Fiction